2021
DOI: 10.1177/1088357620986944
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Versus Concrete: A Comparison of Mathematics Manipulatives for Three Elementary Students With Autism

Abstract: Basic mathematic skills at the early age are foundational for later learning. Many students with autism spectrum disorder (ASD) struggle in academic learning without sufficient support. Research in the area of concrete manipulatives—tangible representations of abstract concepts—has been found effective. In addition, promising research has emerged in the area of virtual manipulatives—virtual representations of abstract concepts—as tools to support mathematics skill acquisition. Using a multiple baseline across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Virtual manipulatives are generally digital representations of concrete manipulatives that are accessible by mobile device apps or internet-based web apps (Bouck, Mathews, & Stenzel, 2020). For students with disabilities in general, researchers suggested virtual manipulatives were just as effective as concrete manipulatives (Peltier et al, 2020; Satsangi et al, 2016; Shurr et al, 2021). Researchers found a preference for virtual manipulatives among secondary students and also suggested some concrete manipulatives can be stigmatizing for secondary students given they are more commonly used with younger students (Satsangi et al, 2016; Satsangi & Miller, 2017).…”
Section: Manipulativesmentioning
confidence: 99%
“…Virtual manipulatives are generally digital representations of concrete manipulatives that are accessible by mobile device apps or internet-based web apps (Bouck, Mathews, & Stenzel, 2020). For students with disabilities in general, researchers suggested virtual manipulatives were just as effective as concrete manipulatives (Peltier et al, 2020; Satsangi et al, 2016; Shurr et al, 2021). Researchers found a preference for virtual manipulatives among secondary students and also suggested some concrete manipulatives can be stigmatizing for secondary students given they are more commonly used with younger students (Satsangi et al, 2016; Satsangi & Miller, 2017).…”
Section: Manipulativesmentioning
confidence: 99%
“…While concrete manipulatives are the most common conceptualization of manipulatives, virtual manipulatives have gained in use over the past decade (Bouck et al, 2020; Root et al, 2021; Satsangi & Miller, 2017; Shurr et al, 2021). Virtual manipulatives are mathematics manipulatives offered in a digital format, such as app or web-based, for use on devices such as computers or tablets (Bouck & Flanagan, 2010; Satsangi & Miller, 2017).…”
Section: Mathematics Manipulativesmentioning
confidence: 99%
“…There is a significant body of literature which supports the use of both virtual (Bouck & Park, 2020 ; Bouck et al, 2020 ; Jimenez & Besaw, 2020 ; Park et al, 2020 ; Root et al, 2021 ) and concrete (Yakubova et al, 2016 , 2020 ) manipulatives for teaching mathematics skills to K-12 autistic students. Although both types of manipulatives have been shown to be effective for teaching mathematics skills to autistic students, past studies that have compared the two types of manipulatives have found that typically students both preferred and performed better with virtual manipulatives (Root et al, 2017 ; Shurr et al, 2021 ). In addition, students have also been shown to complete more problem-solving steps and reach independence faster with virtual compared to concrete manipulatives (Bassette et al, 2019 ; Bouck et al, 2014 ).…”
Section: The Use Of Manipulatives In Mathematics Instructionmentioning
confidence: 99%